RAND in Southeast Asia A History of the Vietnam War Era - Elliott, Mai (RAND Corporation, 2010)
This volume chronicles RAND's involvement in researching insurgency and counterinsurgency in Vietnam, Laos, and Thailand during the Vietnam War era and assesses the effect that this research had on U.S. officials and policies. Elliott draws on interviews with former RAND staff and the many studies that RAND produced on these topics to provide a narrative that captures the tenor of the times and conveys the attitudes and thinking of those involved.